The Wisdom of the Broken Pot: Lessons on Innovation for African American Pastoral Theology - Hinds, Jay-Paul (Theology today (Ephrata, Pa.), 2025)
Ghanaian artist El Anatsui is lauded in the artworld for his innovative sculptures. The unexpected visual experience that his art provides signals, for many art critics, that he is breaking the aesthetic contract that has dominated art and art theory for centuries. This article argues that the art of El Anatsui provides a lesson for African American pastoral theologians searching for innovative ways of doing pastoral theology. The article begins with the impasses that are an inherent part of doing pastoral theology, while also considering the many ways—for example, new resources—that pastoral theologians have used to overcome them. Next, I discuss the role of art and art theory as valuable dialogue partners for pastoral theologians. Lastly, I provide an analysis of the art of El Anatsui and the lessons his sculptures offer to African American pastoral theologians.